Foodstuff analyses show that seafood and water are major perfluoroalkyl acids (PFAAs) sources to humans in Korea - Heo, Jin-Ju; Lee, Ji-Woo; Kim, Seung-Kyu; Oh, Jeong-Eun (Journal of hazardous materials, 2014)
•16 PFAAs in 397 samples of 66 food types and 34 tap water samples were analyzed.•Dietary exposure to PFAAs was estimated by using the PFAAs measured concentrations.•The major contributors of PFAAs dietary exposure were confirmed. We measured concentrations of PFAAs in 397 foods, of 66 types, in Korea, and determined the daily human dietary PFAAs intake and the contribution of each foodstuff to that intake. The PFAAs concentration in the 66 different food types ranged from below the detection limit to 48.3ng/g. Perfluorooctane sulfonate (PFOS) and long-chain perfluorocarboxylic acids (PFCAs) were the dominant PFAAs in fish, shellfish, and processed foods, while perfluorooctanoic acid (PFOA) and short-chain PFCAs dominated dairy foodstuffs and beverages. The Korean adult dietary intake ranges, estimated for a range of scenarios, were 0.60–3.03 and 0.17–1.68ngkg−1bwd−1 for PFOS and PFOA, respectively, which were lower than the total daily intake limits suggested by European Food Safety Authority (PFOS: 150ngkg−1bwd−1; PFOA: 1500ngkg−1bwd−1). The major contributors to PFAAs dietary exposure varied with subject age and PFAAs. For example, fish was a major contributor of PFOS but dairy foods were major contributors of PFOA. However, tap water was a major contributor to PFOA intake when it was the main source of drinking water (rather than bottled water).